2018
DOI: 10.1186/s12989-018-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

All that is silver is not toxic: silver ion and particle kinetics reveals the role of silver ion aging and dosimetry on the toxicity of silver nanoparticles

Abstract: BackgroundWhen suspended in cell culture medium, nano-objects composed of soluble metals such as silver can dissolve resulting in ion formation, altered particle properties (e.g. mass, morphology, etc.), and modulated cellular dose. Cultured cells are exposed not just to nanoparticles but to a complex, dynamic mixture of altered nanoparticles, unbound ions, and ion-ligand complexes. Here, three different cell types (RAW 264.7 macrophages and bone marrow derived macrophages from wild-type C57BL/6 J mice and Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 43 publications
3
43
1
Order By: Relevance
“…This result would be in line with the more limited ability of these larger NPs (when compared to the smaller Au counterparts) to cross the BBB endothelium formed on the surface of the spheroids. Another possible explanation is that they undergo relatively fast dissolution outside and inside the cells (Jiang et al, 2015;Smith et al, 2018). These findings were consistent along different experiments.…”
Section: Polymeric Nanoparticlessupporting
confidence: 86%
“…This result would be in line with the more limited ability of these larger NPs (when compared to the smaller Au counterparts) to cross the BBB endothelium formed on the surface of the spheroids. Another possible explanation is that they undergo relatively fast dissolution outside and inside the cells (Jiang et al, 2015;Smith et al, 2018). These findings were consistent along different experiments.…”
Section: Polymeric Nanoparticlessupporting
confidence: 86%
“…[51][52][53][54] However, there are applications where the presence of Ag + ions is not always desirable. For example, toxicology studies with AgNPs have shown associated cytotoxicity, genotoxicity, and inammatory response in plants, 64 zebrash embryos, 65 and mammalian cell culture models, [66][67][68][69] thereby raising concerns about the potential environmental and human health risks of AgNPs. In these studies, Ag + ions are always present and is a confounding factor making it difficult to interpret data and elucidate how the physicochemical features, shape, size, surface chemistry, and surface area of AgNPs inuence toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, 'all that is silver is not toxic', and recent studies have shown that aging of Ag ions in cell culture medium for 3 or more hours signicantly attenuated toxicity towards a murine macrophage-like cell line. 11 Since Ag nanoparticles are widely used for their antibacterial properties, it is important to determine whether these particles exert any immunosuppressive effects on immune-competent cells. To date, the ndings with regards to the impact of Ag nanoparticles on cells of the innate immune systemthe rst line of cellular defense against microbial infectionare contradictory.…”
mentioning
confidence: 99%